V. V. Mayakovsky in the Literary Heritage of Hrachya Tamrazyan - KHANJYAN, NATALYA (Bulletin of Yerevan University H: Russian Philology, 2021)
The author presents H.Tamrazyan as a distinguished scientist (medievalist) and poet, as well as outstanding translator of Russian poetry into Armenian language. Tamrazyan’s works, editions as a translator of V. Mayakovsky’s, S.Yesenin’s, B.Pasternak’s verses are the subject of special attention. Besides, the author translates and publishes in Russian Tamrazyan’s essay “Early Mayakovsky” (1996), with comments on it.
Keywords: russian poets, the beginning of XX century, translation, essay, Mayakovsky, Tamrazyan